Learn more about

Refine search

Results (displaying matches 1-50 of 3878) Next

Label Class Equation Sato-Tate \(\overline{\Q}\)-simple \(\GL_2\) Rank*
169.a.169.1 169.a \(y^2 + (x^3 + x + 1)y = x^5 + x^4\) $E_6$ 0
277.a.277.1 277.a \(y^2 + (x^3 + x^2 + x + 1)y = -x^2 - x\) $\mathrm{USp}(4)$ 0
277.a.277.2 277.a \(y^2 + y = x^5 - 9x^4 + 14x^3 - 19x^2 + 11x - 6\) $\mathrm{USp}(4)$ 0
324.a.648.1 324.a \(y^2 + (x^3 + x + 1)y = x^5 + 2x^4 + 2x^3 + x^2\) $E_3$ 0
349.a.349.1 349.a \(y^2 + (x^3 + x^2 + x + 1)y = -x^3 - x^2\) $\mathrm{USp}(4)$ 0
353.a.353.1 353.a \(y^2 + (x^3 + x + 1)y = x^2\) $\mathrm{USp}(4)$ 0
388.a.776.1 388.a \(y^2 + (x^3 + x + 1)y = -x^4 + 2x^2 + x\) $\mathrm{USp}(4)$ 0
461.a.461.1 461.a \(y^2 + x^3y = x^5 - 3x^3 + 3x - 2\) $\mathrm{USp}(4)$ 0
461.a.461.2 461.a \(y^2 + y = x^5 - x^4 - 39x^3 + 10x^2 + 272x - 306\) $\mathrm{USp}(4)$ 0
484.a.1936.1 484.a \(y^2 + y = x^6 + 2x^4 + x^2\) $G_{3,3}$ 0
529.a.529.1 529.a \(y^2 + (x^3 + x + 1)y = -x^5\) $G_{3,3}$ 0
597.a.597.1 597.a \(y^2 + y = x^5 + 2x^4 + 3x^3 + 2x^2 + x\) $\mathrm{USp}(4)$ 0
604.a.9664.1 604.a \(y^2 + (x^2 + x + 1)y = 4x^5 + 9x^4 + 48x^3 - 4x^2 - 53x - 21\) $\mathrm{USp}(4)$ 0
604.a.9664.2 604.a \(y^2 + (x^3 + 1)y = -x^4 + x^3 + x^2 - x\) $\mathrm{USp}(4)$ 0
676.a.5408.1 676.a \(y^2 + (x^3 + x^2 + x)y = x^3 + 3x^2 + 3x + 1\) $G_{3,3}$ 0
676.a.562432.1 676.a \(y^2 + (x^3 + 1)y = 2x^5 + 2x^4 + 4x^3 + 2x^2 + 2x\) $G_{3,3}$ 0
676.b.17576.1 676.b \(y^2 + (x^2 + x)y = -x^6 + 3x^5 - 6x^4 + 6x^3 - 6x^2 + 3x - 1\) $E_1$ 0
713.b.713.1 713.b \(y^2 + (x^3 + x + 1)y = -x^4\) $\mathrm{USp}(4)$ 0
745.a.745.1 745.a \(y^2 + (x^3 + x + 1)y = -x\) $\mathrm{USp}(4)$ 0
797.a.797.1 797.a \(y^2 + y = x^5 - x^4 + x^3\) $\mathrm{USp}(4)$ 0
841.a.841.1 841.a \(y^2 + (x^3 + x^2 + x)y = x^4 + x^3 + 3x^2 + x + 2\) $G_{3,3}$ 0
862.b.862.1 862.b \(y^2 + (x^3 + x)y = -2x^4 + 3x^2 - x - 1\) $\mathrm{USp}(4)$ 0
886.a.3544.1 886.a \(y^2 + (x^3 + x)y = -x^4 - x + 1\) $\mathrm{USp}(4)$ 0
961.a.961.3 961.a \(y^2 + (x^3 + x + 1)y = x^5 + x^4 + x^3 - x - 1\) $G_{3,3}$ 0
961.a.923521.1 961.a \(y^2 + (x^3 + x^2 + 1)y = -5x^4 + 4x^3 + 3x^2 - 2x - 3\) $G_{3,3}$ 0
976.a.999424.1 976.a \(y^2 + (x + 1)y = x^6 - 2x^5 + 2x^3 - x^2\) $\mathrm{USp}(4)$ 0
1012.a.4048.1 1012.a \(y^2 + (x^3 + 1)y = x^4 + x^3 + x^2 + x\) $\mathrm{USp}(4)$ 0
1042.a.1042.1 1042.a \(y^2 + (x^3 + x)y = -x^4 - x^3 - x^2 + 2x + 2\) $\mathrm{USp}(4)$ 0
1069.a.1069.1 1069.a \(y^2 + (x^2 + x + 1)y = x^5 + x^3\) $\mathrm{USp}(4)$ 0
1077.b.1077.1 1077.b \(y^2 + x^3y = x^5 + x^4 - x - 2\) $\mathrm{USp}(4)$ 0
1077.b.1077.2 1077.b \(y^2 + y = x^5 + 14x^4 + 38x^3 - 79x^2 + 15x - 1\) $\mathrm{USp}(4)$ 0
1109.a.1109.1 1109.a \(y^2 + y = x^5 - 6x^4 - 36x^3 - 6x^2 + 63x - 36\) $\mathrm{USp}(4)$ 0
1109.b.1109.1 1109.b \(y^2 + y = x^5 - x^4 - x^3 + x^2 + x\) $\mathrm{USp}(4)$ 0
1109.c.1109.1 1109.c \(y^2 + (x^3 + x)y = x^5 - 2x^3 - 2x^2 - 1\) $\mathrm{USp}(4)$ 0
1116.a.214272.1 1116.a \(y^2 + (x^3 + 1)y = x^4 + 2x^3 + x^2 - x\) $\mathrm{USp}(4)$ 0
1164.a.1164.1 1164.a \(y^2 + (x^3 + 1)y = -x^4 + x^2 - 1\) $\mathrm{USp}(4)$ 0
1164.b.670464.1 1164.b \(y^2 + (x^2 + x + 1)y = 2x^5 - 2x^4 + x^3 - x^2\) $\mathrm{USp}(4)$ 0
1210.a.1210.1 1210.a \(y^2 + (x^3 + x)y = 3x^3 - 2x^2 + 6x + 2\) $G_{3,3}$ 0
1231.a.1231.1 1231.a \(y^2 + (x^3 + 1)y = -x^4 + 2x^2 - x - 2\) $\mathrm{USp}(4)$ 0
1285.a.1285.1 1285.a \(y^2 + y = x^5 - 2x^4 + 3x^3 - x\) $\mathrm{USp}(4)$ 0
1444.a.46208.1 1444.a \(y^2 + (x^3 + 1)y = x^5 - 4x^3 + x\) $G_{3,3}$ 0
1444.b.109744.1 1444.b \(y^2 + x^3y = -4x^4 + 16x^2 - 19\) $G_{3,3}$ 0
1468.b.5872.1 1468.b \(y^2 + (x^2 + x + 1)y = -2x^5 - 2x^4\) $\mathrm{USp}(4)$ 0
1532.a.1532.1 1532.a \(y^2 + (x^3 + 1)y = -x - 1\) $\mathrm{USp}(4)$ 0
1532.a.392192.1 1532.a \(y^2 + (x^2 + x + 1)y = x^5 + 7x^4 - 53x^2 + 12x - 1\) $\mathrm{USp}(4)$ 0
1589.a.1589.1 1589.a \(y^2 + y = x^5 + 4x^4 + 4x^3 - x^2 - x\) $\mathrm{USp}(4)$ 0
1665.a.1665.1 1665.a \(y^2 + (x^3 + x^2 + 1)y = x^4 + x^3 + 2x^2 + 2x + 1\) $\mathrm{USp}(4)$ 0
1696.b.434176.1 1696.b \(y^2 + xy = x^6 - 2x^5 + 2x^4 + 9x^3 - 12x^2 + 3x + 26\) $N(G_{3,3})$ 0
1701.a.1701.1 1701.a \(y^2 + y = x^5 + 19x^4 + 86x^3 - 60x^2 + 12x - 1\) $\mathrm{USp}(4)$ 0
1811.b.1811.1 1811.b \(y^2 + x^3y = x^5 + x^4 - x^3 - 3x^2 - x + 2\) $\mathrm{USp}(4)$ 0
Next

Download all search results for